Kilt at the highland games - Dunnett, Kaitlyn (Dunnett, Kaitlyn. Liss MacCrimmon mystery., 2016)
It's July in Moosetookalook, Maine, and Scottish Emporium proprietress Liss MacCrimmon Ruskin is prepping her wares for the annual Celtic heritage festival. But as a sinister crime wave washes over the quiet town, this year's celebration might prove a wee bit more eventful - and deadly - than tartan and bagpipes.